Pozytywne i negatywne skutki napływu kapitału zagranicznego do polskiego systemu bankowego w latach dziewięćdziesiątych - Gładysz, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
Before 1990, Polish banks were characterized by capital shortage, lack of competition, narrow range of the financial products and services offered as well as by low level of bank staff qualifications. The entrance of either foreign banks or foreign investments solves these problems but also results in some risks such as a loss of the authorities' control over the banking system, the deterioration of the domestic entities position and the others. The paper shows positive and negative effects of the foreign capital inflow into the Polish banking sector in the 1990's. It is very important issue since the large scale of foreign direct investments engaged in the financial sector in Poland.